ANALYSIS OF MEKAAR BUSINESS DEVELOPMENT STRATEGY OF PT PERMODALAN NASIONAL MADANI (PERSERO) - Setyawati, Ika; Jahroh, Siti; Djohar, Setiadi (Jurnal Aplikasi Manajemen, 2020)
This research analyzed about Mekaar business development strategy at PT Permodalan Nasional Madani (Persero) to find out Mekaar business unit's developmental strategy to improve the living standard of poor people in Indonesia of the customers who have joined it, to find out Mekaar financing business unit (performance) based on strengths, weaknesses, opportunities, and threats, and also to determine business strategies that can be used to develop Mekaar program. This study applies descriptive and SFAS analysis methods. SFAS analysis method is a summary of the analysis of strategic factors obtained based on the analysis results of internal (IFAS) and external (EFAS) factors. One of the results of this study showed the strategies that must be taken include: support for the provision of access to capital, increased penetration of service coverage, employee recruitment as needed, government support through MSME policy, implementation of market research related to customer needs, provision of non- material stimulus for employees, and funding diversification. Based on the conclusion of the study, for the next research, the writer recommends measuring the success of the strategies carried out by the company based on the level of stakeholder satisfaction and the expectations of the people served.